1997
DOI: 10.1128/mcb.17.7.4096
|View full text |Cite
|
Sign up to set email alerts
|

HRS/SRp40-Mediated Inclusion of the Fibronectin EIIIB Exon, a Possible Cause of Increased EIIIB Expression in Proliferating Liver

Abstract: Serine-arginine (SR)-rich proteins are believed to be important in mediating alternative pre-mRNA splicing. HRS/SRp40 expression is elevated in liver cell proliferation during development, regeneration, and oncogenesis. We tested whether HRS expression correlates with the appearance of alternatively spliced fibronectin transcripts during liver growth. HRS was highly expressed during the proliferative phase of liver development, correlating with expression of the fibronectin EIIIB alternative exon. In regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 50 publications
(71 reference statements)
7
59
0
Order By: Relevance
“…Nevertheless, it is important to point out that not all alternatively spliced regions are subjected to transcriptional control. For example, inclusion levels of the alternatively spliced EDII exon of human fibronectin (also named EDB and EIIIB) are not affected by promoter swapping, transcription factor activation, or the slow polymerase but are stimulated by overexpression of the SR protein Srp40 (27). This indicates that control by SR proteins might or might not coexist with transcriptional control.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, it is important to point out that not all alternatively spliced regions are subjected to transcriptional control. For example, inclusion levels of the alternatively spliced EDII exon of human fibronectin (also named EDB and EIIIB) are not affected by promoter swapping, transcription factor activation, or the slow polymerase but are stimulated by overexpression of the SR protein Srp40 (27). This indicates that control by SR proteins might or might not coexist with transcriptional control.…”
Section: Discussionmentioning
confidence: 95%
“…Primary antibody anti-Egr 1 antiserum (Santa Cruz Biotechnology) was diluted 1:1000 and incubated with the membrane for 1 h at room temperature. Horseradish peroxidase-linked secondary antibody was added at a dilution of 1:10000 for 30 min and then detected by chemiluminescence (Amersham Pharmacia Biotech) according to the instructions of the manufacturer (27).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Taub and co-workers (40) first cloned the SR protein, SRp40/HRS, using a subtractive cDNA library in a model of regenerating rat liver responsive to insulin. Subsequently, they showed that this increase in the expression of SRp40 in response to insulin was required for the inclusion of exon EIIIB of the fibronectin gene (22). Krainer and co-workers (34) demonstrated that increased levels of SRp30a during T-cell activation correlated with changes in the alternative splicing patterns of CD44 and CD45 pre-mRNA.…”
Section: Extracts From Hela Cells (Data Not Shown)mentioning
confidence: 99%
“…Several studies in the literature (22,34,40) demonstrate that changes in the level of expression of SR proteins in response to growth factors and cellular proliferation can also regulate the alternative splicing of specific pre-mRNAs. For example, Taub and co-workers (40) first cloned the SR protein, SRp40/HRS, using a subtractive cDNA library in a model of regenerating rat liver responsive to insulin.…”
Section: Extracts From Hela Cells (Data Not Shown)mentioning
confidence: 99%
See 1 more Smart Citation